2022
DOI: 10.1108/ijbm-07-2021-0305
|View full text |Cite
|
Sign up to set email alerts
|

Research on financial innovations: an interdisciplinary review

Abstract: PurposeThe financial industry offers a unique setting to study innovations. Financial innovations have fueled the growth of economies, markets and societies. The financial industry has successfully become the breeding ground for innovative services, processes, business models and technologies. This study seeks to provide a holistic view of the literature on financial innovations, synthesize the research findings and offer future directions for research in light of three market developments that are disrupting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 124 publications
(240 reference statements)
2
41
0
1
Order By: Relevance
“…Based on the focus of previous studies, financial innovation is defined as one of the following: new product, new service, new product process or new organisation form (Chen & Peng, 2020, p. 308; Frame & White, 2004, p. 118; Nejad, 2022, p. 579). Investigating improvement in performance brought about by the introduction of a new service ties into what (Nejad, 2022) describes as the ‘outcome’ of innovation.…”
Section: Review Of Literature and Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the focus of previous studies, financial innovation is defined as one of the following: new product, new service, new product process or new organisation form (Chen & Peng, 2020, p. 308; Frame & White, 2004, p. 118; Nejad, 2022, p. 579). Investigating improvement in performance brought about by the introduction of a new service ties into what (Nejad, 2022) describes as the ‘outcome’ of innovation.…”
Section: Review Of Literature and Hypothesismentioning
confidence: 99%
“…Based on the focus of previous studies, financial innovation is defined as one of the following: new product, new service, new product process or new organisation form (Chen & Peng, 2020, p. 308; Frame & White, 2004, p. 118; Nejad, 2022, p. 579). Investigating improvement in performance brought about by the introduction of a new service ties into what (Nejad, 2022) describes as the ‘outcome’ of innovation. This is where a new product, service, process, or business model is meant to reduce costs, improve performance, and capabilities, offer new ways of addressing customer needs, extend functionality, and so forth (Nejad, 2022, p. 582).…”
Section: Review Of Literature and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…This is best summed up by M. Blake (2021), Head of Financial and Monetary Systems, World Economic Forum: "Despite this challenging backdrop, FinTechs have proven resilient and adaptable: contributing to pandemic relief efforts, adjusting operations and offerings to serve vulnerable market segments, like micro, small and medium-sized businesses, while posting year-over-year growth across most regions" (p.1). Namely, the pandemic has shown that fintech companies have access to more individuals, lower the cost of financial services, and that they reduce the need for face-to-face interactions (Nejad, 2022). The following graph shows the value of services of key fintech companies during the first six months of 2020 as compared to the same period in 2019.…”
Section: Impact Of the Pandemic On Fintech Companies And Financial In...mentioning
confidence: 99%
“…With the extended duration of the pandemic, it is reasonable to expect a further growth in demand for digital lending because cash reserves will be exhausted. Nejad (2022) showed that fintech companies significantly changed their business models during the pandemic, i.e. "two-thirds of firms said they had changed their business model in response, including by reducing fees, changing qualification criteria, and easing payment requirements, about 60 percent reported launching new products and value-added services, such as offering information, forty percent of firms surveyed indicated that they have either introduced or are in the process of introducing enhanced fraud or security measures as a response to business conditions under the pandemic. "…”
Section: Impact Of the Pandemic On Fintech Companies And Financial In...mentioning
confidence: 99%